Pengaruh Kompetensi Sumber Daya Manusia, Motivasi dan Lingkungan Kerja pada Komitmen Organisasi dan Implikasinya pada Kinerja Pengurus Barang Pemerintah Kabupaten Tabanan - Ayu Yuliantini, Putu; Putra Astika, Ida Bagus; Badera, Dewa Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.10.TAHUN 2017DO - 10.24843/EEB.2017.v06.i10.p10, 2017)
The purpose of this study was to obtain empirical evidence related to the effect of the competence of human resources (HR), motivation and work environment on organizational commitment and its implications on the administrators assets performance in government of Tabanan regency. Data used in this study are primary data obtained from respondents through a survey method using a questionnaire. The population consisted of 47 administrators assets in Regional Work Unit of Tabanan Regency . Sampling technique using purposive sampling and obtained a sample of 41 people. Analysis of the data using SmartPLS version 3.2.4 m3 through outer model, inner model and hypothesis testing. Outer model and inner model show the results of all the research instruments are valid and reliable and feasible models used to explain the endogenous variables. HR competence, motivation and work environment has direct influence on organizational commitment and the administrators assets performance . Motivation and work environment have an impact indirectly on the administrators assets performance through the organizational commitment while the influence of HR competencies in administrators assets performance is not mediated by organizational commitment.